Antimicrobial Susceptibility Pattern among Patients Presenting with Acute Exacerbation of COPD - Amer Zohaib; Fahad Aman Khan; Imran Khan; Mukhtar Ahmad; Talha Khalid; Tashia Malik; Khawar Siddique; Sidra Munir; Muhammad Saeed (Journal of Islamabad Medical and Dental College, 2020)
Background: The irrational use of antibiotics in outpatient as well as indoor patients without studying the culture and sensitivity patterns may have led to resistance in common organisms causing acute exacerbation of chronic obstructive pulmonary disease. The objective of this study was to determine the culture and sensitivity patterns of bacteria in the sputum of patients presenting with acute exacerbation of chronic obstructive pulmonary disease (COPD) in our population. Material and Methods: This cross-sectional study was conducted in the Medicine Department, Jinnah Hospital Lahore from 1st January 2018 to 25th June 2018. A total of 215 patients with acute exacerbation of COPD were collected through non-probability consecutive sampling technique. COPD was diagnosed on the basis of history, examination, chest X-ray and spirometry. Acute exacerbation was taken as an acute rise in one or more of the following; sputum volume and/or purulence, frequency and severity of cough and dyspnea. Two sputum samples were collected from each patient. Antimicrobial susceptibility testing was done as per CLSI guidelines. Data was analyzed by SPSS version 21.0. with p-value ≤ 0.05 considered as statistically significant. Results: Among 215 selected cases, 118 (54.88%) were males and 97 (45.12%) were females. A total of 110 (51.16%) cultures were positive and 105 (48.84%) were negative for bacterial growth. Klebsiella pneumoniae (n=69; 62.72%) was the most frequent microorganism in patient’s sputum followed by Pseudomonas aeruginosa (n=21; 19.1%) and Staphylococcus aureus (n=20; 18.2%). Regarding sensitivity pattern, amikacin was found to be the most sensitive antibiotic against these organisms followed by gentamicin and ciprofloxacin. Conclusion(s): Klebsiella pneumoniae was the most common microorganism in the sputum of patients presenting with acute exacerbation of COPD, while amikacin was reported to be most sensitive antibiotic against the microorganism.